Microbiological food safety in Malaysia from the academician’s perspective - New, C.Y.,; Ubong, A.; Premarathne, J.M.K.J.K.,; Thung, T.Y.,; Lee, E.,; Chang, W.S.,; Loo, Y.Y.; Kwan, S.Y.; Tan, C.W.; Kuan, C.H.; Son, R. (Food Research, 2017)
Food safety in Malaysia is not considered an issue yet. From the previous year (2005- 2015) records, the incidence rate of food poisoning had been fluctuating and despite that, cases continue to occur especially among school students. As a developing nation, it is high-time that Malaysia begins to emphasize on food safety to reduce the burden of foodborne illness in the socio-economic development of the country, and at the same time, gain benefits in terms of economic returns and trade through food safety enforcement. Most importantly, public health is achieved through food safety implementation and accentuation. The current standing point of the Malaysia’s food safety is discussed in this review. In addition, the review will also discuss the role of academicians as intervention contributions in tackling food safety issues. The review is hoped to provide valuable and concentrated information and knowledge to readers in the light to drive Malaysia into ensuring safer food for the public.